EFEKTIVITAS PENGGUNAAN KOMIK DIGITAL BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR IPAS KELAS III SDN 1 KUWUKAN: EFEKTIVITAS PENGGUNAAN KOMIK DIGITAL BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR IPAS KELAS III SDN 1 KUWUKAN - Ayu Paramastuti; Imaniar Purbasari; Khamdun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study investigates the effectiveness of local wisdom-based digital comics on Natural and Social Sciences (IPAS) learning outcomes among third-grade students at SDN 1 Kuwukan. The research employed a quasi-experimental design with one group pretest-posttest design involving 15 students as subjects. The digital comic media integrated local wisdom elements from Kuwukan Village, including Sewu Kupat Tradition, Barongan Art, village environmental conditions, gotong royong values, and traditional kupat food. Data collection utilized validated and reliable learning outcome tests with expert validation showing 95.45% validity in the "very valid" category and Cronbach's Alpha reliability of 0.892. Results demonstrated highly significant effectiveness through paired sample t-test (t = -16.000; p < 0.001), showing an average score increase of 26.67 points from pretest (62.33) to posttest (89.00). The N-Gain score achieved 70.73% in the "high" category, with 53.33% of students reaching high category and 46.67% reaching medium category. Effect size calculation (Cohen's d = 4.133) indicated a very large practical impact. The integration of local wisdom proved to provide meaningful learning experiences by connecting learning materials with students' daily life contexts. Digital comic media demonstrated several advantages including high visual appeal, usage flexibility, ability to concretize abstract concepts, and potential for interactive learning. These findings support multimedia learning theory and constructivist approaches in elementary education. The study concludes that local wisdom-based digital comics are highly effective for improving IPAS learning outcomes and can serve as an innovative alternative for elementary science education.